2023
DOI: 10.1017/dsj.2023.7
|View full text |Cite
|
Sign up to set email alerts
|

Idea evaluation as a design process: understanding how experts develop ideas and manage fixations

Abstract: Idea evaluation is used to identify and select ideas for development as future innovations. However, approaching idea evaluation as a decision gate can limit the role of the person evaluating ideas, create fixation bias, and underutilise the person’s creative potential. Although studies show that during evaluation experts are able to engage in design activities, it is still not clear how they design and develop ideas. The aim of this study was to understand how experts develop ideas during evaluation. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Even though no beyond-frame search is enhanced, an advancement in other aspects could still be achieved as long as there is an expansion within the existing frame. This conclusion is supported by a study conducted by Boudier et al (2023), which suggested that experts in the evaluation of design ideas either contribute to the development of a design solution within the frame constructed by the initial idea, or to the engagement in defixation by initiating alternative solutions beyond the existing frame. Accordingly, to ensure the effectiveness of the defixation approach to open-ended problems, an examination of the influence on both fixation and the measures that are related to the aim of the specific study is necessary to identify whether there is an enhancement in beyond-frame searches or within-frame searches.…”
Section: Defixation Approach For Fixation Induced By Problem Informat...mentioning
confidence: 85%
“…Even though no beyond-frame search is enhanced, an advancement in other aspects could still be achieved as long as there is an expansion within the existing frame. This conclusion is supported by a study conducted by Boudier et al (2023), which suggested that experts in the evaluation of design ideas either contribute to the development of a design solution within the frame constructed by the initial idea, or to the engagement in defixation by initiating alternative solutions beyond the existing frame. Accordingly, to ensure the effectiveness of the defixation approach to open-ended problems, an examination of the influence on both fixation and the measures that are related to the aim of the specific study is necessary to identify whether there is an enhancement in beyond-frame searches or within-frame searches.…”
Section: Defixation Approach For Fixation Induced By Problem Informat...mentioning
confidence: 85%
“…A jury of five industry and research specialists evaluated the product’s quality. The subjective nature of this assessment introduces the possibility of individual biases affecting the scoring and ranking of the products (Stylidis, Wickman, & Söderberg 2020; Boudier et al 2023). Biases can be observed, as professionals in the industry tend to overestimate the significance of attributes they are currently focusing on (Stylidis et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were made to address this limitation by appointing a diverse jury with individuals from different backgrounds. The industry experts provided explicit feedback to the teams and posed questions after their presentations, following the recommendation of Boudier et al (2023). However, it is essential to acknowledge that biases cannot be eliminated entirely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation